IDOMA PROVERBIAL NAMES AS A VEHICLE OF EXPRESSION: A SOCIOLINGUISTIC VIEW - Amali, Halima; Ciroma, Zainab; Bashir, Amina (Proverbium - Yearbook, 2019)
This paper is a presentation and analysis of proverbial names of the Idoma people of Nigeria. A total of fourteen proverbial names are written in Idoma, translated into and analyzed in English within the purview of literature and Sociolinguistics. Proverbial names, and names in general, like proverbs are a vehicle for expression in apt language and are considered an important aspect of the Idoma oral lore. The analysis reveals that Idoma proverbial names are a vehicle of expression and convey very deep meaning and interpretations. They also serve didactic purposes where a name advises against societal ills or suggesting the need for people to embrace humility as the case may be. Socio-linguistically, these proverbial names are not just arbitrary labels but socio-cultural tags with their functions and meanings. Proverbs and proverbial names therefore stand as the fortress and custodian of the people’s wisdom.